Carbapenem-resistant Klebsiella pneumoniae infections in a Greek intensive care unit: Molecular characterisation and treatment challenges. Issue 2 (June 2015) - Katsiari, Maria; Panagiota, Giakkoupi; Likousi, Sophia; Roussou, Zoi; Polemis, Michalis; Alkiviadis Vatopoulos, C.; Evangelia Platsouka, D.; Maguina, Asimina
Highlights: Most of the carbapenemase-producing Klebsiella pneumoniae were KPC-2-producing isolates belonging to clone ST258. K. pneumoniae isolates were multidrug- or extensively drug-resistant. Infection mortality was significantly high. Isolate survival in patients' normal flora serves as a reservoir for transmission. 'Cycling' of patients colonised with KPC-producing strains creates 'resistance loops'. Abstract: Acquisition of carbapenemase-producing Klebsiella pneumoniae (CP-Kp) strains poses a major threat to critically ill patients. The objectives of this study were to describe the epidemiology of CP-Kp isolates as well as the clinical outcome associated with the corresponding infections and to identify risk factors for mortality of intensive care unit (ICU) patients in a Greek hospital. A prospective, observational study was conducted in a nine-bed general ICU over a 2-year period (April 2010–March 2012). Imipenem-resistant K. pneumoniae isolates recovered from clinical samples of ICU patients were prospectively collected and studied for the presence of carbapenemases. Isolates were submitted to molecular typing using pulsed-field gel electrophoresis (PFGE). In total, 61 CP-Kp isolates (48 KPC-producers and 13 VIM-producers) were recovered from 58 ICU patients. The majority of KPC-producers were classified into a single PFGE type, indicating potent clonal dissemination. Among the 32 infected patients, bacteraemia was diagnosed in 16. Tigecycline + colistin was the most common combination antimicrobial regimen. Infection-attributable mortality was 43.8%. Regarding mortality risk factors, non-survivors were older ( P  = 0.080), all of them presented with septic shock ( P  = 0.010) and they had higher Sepsis-related Organ Failure Assessment (SOFA) scores at infection onset ( P  = 0.004) compared with survivors. Appropriate definitive treatment and combination regimens were not associated with patient survival. In conclusion, CP-Kp infections are associated with limited treatment options and high in-hospital mortality. Effective measures for preventing dissemination of respective isolates in the hospital setting are required.